Relative deprivation and mortality - a longitudinal study in a Swedish population of 4,7 million, 1990-2006 - Åberg Yngwe Monica; Kondo Naoki; Hägg Sara; Kawachi Ichiro (BMC, 2012)
Abstract Background Relative deprivation has previously been discussed as a possible mechanism underlying the income-health relation. The idea is that income matters to the individual's health, over and above the increased command over resources, as the basis of social comparisons between a person and his or her reference group. The following study aimed to analyze the role of individual-level relative deprivation for all-cause mortality in the Swedish population. The Swedish context, characterized by relatively small income inequalities and promoting values as egalitarianism and equality, together with a large data material provide unique possibilities for analyzing the hypothesized mechanism. Methods The data used are prospective longitudinal data from the Swedish population and based on a linkage of registers. Restricting selection to individuals 25-64 years, alive January 1st 1990, gave 4.7 million individuals, for whom a mortality follow-up was done over a 16-year period. The individual level relative deprivation was measured using the Yitzhaki index, calculating the accumulated shortfall between the individual's income and the income of all other's in the person's reference group. All-cause mortality was used as the outcome measure. Results Relative deprivation, generated through social comparisons, is one possible mechanism within the income and health relation. The present study analyzed different types of objectively defined reference groups, all based on the idea that people compare themselves to similar others. Results show relative deprivation, when measured by the Yitzhaki index, to be significantly associated with mortality. Also, we found a stronger effect among men than among women. Analyzing the association within different income strata, the effect was shown to be weak among the poorest. Revealing the importance of relative deprivation for premature mortality, over and above the effect of absolute income, these results resemble previous findings. Conclusion Relative deprivation, based on social comparisons of income, is significantly associated with premature mortality in Sweden, over and above the effect of absolute income. Also, it was found to be more important among men, but weak among the poorest.